Poetry and territory in José María Arguedas: The Andean ecopoetics of Deep Rivers - Favaron Peyón, Pedro Martín (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article attempts to rethink Deep Rivers (1958) by José María Arguedas (1911-1969) from the ecological concerns that mark our time, in order to account for the irreplaceable contribution and relevance of the Andean writer and anthropologist. The aim is to carry out an ecopoetic hermeneutic of Arguedas’ novel, in conversation with some of his anthropological and linguistic reflections, and highlighting some particular aspects of his biography. Arguedas’ ecological reflection draws on indigenous sensitivity and an understanding of all living beings as bearers of conscience, affection and language. In this way, Arguedas’ work opens epistemologies and ontologies that, far from the hegemonic paradigm of scientistic and positivist modernity, conceive of the profound and intimate interdependence of the human being with the sacred fabric of life.